Control of shunt-wound motors with DC/DC converters using the pole placement technique - Nadheer Abdulridha Shalash; Wameedh Riyadh Abdul-Adheem; Yasir Khaldoon Abdul Jabbar (Institute of Advanced Engineering and Science, 2022)
Many techniques have been developed for the speed manipulation of shunt-wound direct current motors (SWDCMs) established based on armature and field control. The current research proposes a controller based on the pole placement (PP) control technique and compares it with a proportional integral (PI) controller for trajectory speed control of SWDCM with uncertainty. The circuit of the DC/DC converters energizes the DC motor. The responses are analyzed according to the dynamic mathematical model of the implemented controllers and the model of the DC/DC converters. Comparison of the motor dynamical response of the conventional PI and proposed PP controllers indicates that the PP controller exhibits improved performance in terms of rise time and steady-state error